PEMETAAN KEPADATAN JENTIK DAN KASUS DBD DI WILAYAH KERJA PUSKESMAS MERTOYUDAN I KABUPATEN MAGELANG - Irva Rahmi Yuliasari; Mateus Sakundarno Adi; M. Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The Mertoyudan I health center area is an endemic area of dengue. One of factors that influence the incidence of DHF are density larvae. There is no mapping of density larvae and DHF cases in the work area of the Mertoyudan Health Center I. The purpose of this study is to describe and map the density of larvae and DHF case in the working area of Mertoyudan I health center. This study is a descriptive study using cross sectional study design with a spatial approach. Samples taken 100 houses using sampling with probability proportional to size method. The mapping results, 2 villages had medium larvae density, 2 villages had medium larvae density and 1 village had high larvae density. Suggestions for the community to pay more attention to cleanliness of water reservoirs in the area around the house that are potential for breeding larvae Aedes sp.